An ultrastructural comparison of dermo-epidermal separation techniques. - Willsteed, E; Bhogal, B; Das, A; Bekir, S; Wojnarowska, F; Black, M; Mckee, P (1991)
Dermo-epidermal separation through the lamina lucida is an essential technique for immunoblotting studies and for the diagnostic immunofluorescence of autoimmune bullous diseases. The most widely used methods of producing skin separation in the laboratory are suction blister induction and incubation in 1 molar sodium chloride. More recently the use of a proteolytic enzyme, thermolysin, has been described for this purpose. We examined the electron microscopic appearance of five suction blisters, five skin specimens separated by 1 M NaCl, and five treated with thermolysin. Both suction blister formation and treatment with 1 M NaCl resulted in a clean separation through the lamina lucida in all specimens examined. However specimens treated with thermolysin developed intra-epidermal separation in four cases without any lamina lucida separation in three. Suction blister formation was associated with hemidesmosome disruption. Incubation in 1 M NaCl remains the most reproducible, convenient, and reliable method of producing dermo-epidermal separation in the laboratory.